One-stop directory for Perak development projects / Wan Rabiah Wan Omar, Arina Rahmat and Suharto Teriman - Wan Omar, Wan Rabiah; Rahmat, Arina; Teriman, Suharto (2022)
Development Plans are legal, gazetted documents produced under the jurisdiction of the Town and Country Planning Act 1976 (Act 172). Four development plan hierarchies aim to guide development at federal, regional, state, and local government levels. In the Perak state, there are currently 22 development plans consisting of one Northern Region Economic Development Strategic Plan (NCER) 2021-2025, one Perak State Structure Plan 2040, 14 Local Plans and five Special Areas Plans. Each Development Plan report has 50 to 150 development projects recommended for implementation over the next 15 years. These proposed projects include commercial, residential, industrial, environmental, infrastructure, and community amenities projects. These 22 separate documents have a total of 1053 project recommendations. This presents a considerable challenge to state officials, particularly EXCOs and implementing agencies, as it necessitates thoroughly examining all these documents. The One-Stop Directory for Perak Development Projects was created to solve this issue, which serves as a starting resource for review or evaluation. This innovative One-Stop Directory contains all project recommendations gathered from all 22 documents in a Matrix Table that displays the project's basic information, including Project Name, Project Component, Location, and original reference source including the document’s name and page number. This invention is intended to achieve an efficient monitoring system that will speed up the completion of all Development Project proposals. This technique permits oversight by the Chief Minister on the EXCO Committee and government agencies because each project has a Lead Executor and Joint Executor. A systematic database is required to record the planning and monitor the status of each project's execution according to the Key Executors to ensure that this strategy can be implemented smoothly.